Answer:
y = -0.2243
OR
y =
- 1.57
Explanation:
Step 1 - simplify the equation:
7* -2y = -14y
3.14 = -14y
Step 2 - Divide both sides of the equation by -14:
![(3.14)/(-14) = (-14y)/(-14)](https://img.qammunity.org/2022/formulas/mathematics/high-school/5keu4cpy91ciaiv4lfhk87lih82fc274zz.png)
-0.2243 = y
Or if the equation contains two variables (3.14 = 7x - 2y):
Step 1 - Add 2y to both sides of the equation
3.14 + 2y = 7x - 2y + 2y
3.14 + 2y = 7x
Step 2 - Subtract 3.14 from both sides of the equation:
3.14 + 2y - 3.14 = 7x - 3.14
2y = 7x - 3.14
Step 3 - Divide both sides of the equation by 2:
![(2y)/(2) = (7x)/(2) - (3.14)/(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/wmr1cdebdmubujlxyavzkxgqaatj7nkra8.png)
y = \frac{7x}{2} - 1.57
Hope this helps!